Mycobacterium tuberculosis Infection Induces Low-Density Granulocyte Generation by Promoting Neutrophil Extracellular Trap Formation via ROS Pathway - Su, Rigu; Peng, Yi-ping; Deng, Zhen; Deng, Ya-ting; Ye, Jianq-qing; Guo, Yang; Huang, Zi-kun; Luo, Qing; Jiang, Hong; Li, Jun-ming (Frontiers in Microbiology, 2019)
The roles and characteristics of LDGs have recently attracted attention; however, the mechanism of the formation of LDGs is yet unclear. In one of our previous studies, the frequency of LDGs was significantly elevated in the peripheral blood of tuberculosis patients, and in situ activation contributed to the generation of LDGs upon Mycobacterium tuberculosis infection. However, the underlying molecular mechanisms are yet to be elucidated. In the present study, the release of NETs and the levels of ROS were regulated before the NDGs to be infected with M. tuberculosis, and the conversion of NDGs to LDGs was monitored subsequently as well. The results showed that tuberculosis-related LDGs spontaneously released high levels of NETs. Promoting the release of NETs led to increase the conversion of NDGs to LDGs in M. tuberculosis infection, while inhibiting the release of NETs suppressed this conversion after the infection. The M. tuberculosis infection significantly increased the ROS levels in neutrophils and the conversion of NDGs to LDGs. Scavenging ROS or blocking the ROS generation of M. tuberculosis-infected NDGs significantly suppressed the release of NETs and blocked the generation of LDGs. Moreover, inhibiting the formation of NETs without affecting the levels of ROS significantly decreased the conversion of NDGs to LDGs after M. tuberculosis infection. Overall, this study demonstrated that M. tuberculosis could induce the generation of LDGs by promoting the release of NET via ROS pathway.